2002
DOI: 10.1046/j.1365-2664.2002.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

The selection of stubble fields by wintering granivorous birds reflects vegetation cover and food abundance

Abstract: Summary 1.Fields left fallow after harvest (i.e. stubble fields) support high wintering densities of many species of granivorous bird. We examined correlates of use by eight such species of different types of intensively managed wheat and barley stubble fields, organic wheat fields and set-aside fields on mixed lowland farmland in central England. Field occupancy was studied in relation to the physical characteristics of fields and seed abundance. 2. Higher seed abundance was associated with greater occupancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
149
1
30

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 33 publications
14
149
1
30
Order By: Relevance
“…Meadow Pipit has also exhibited a population decline and has been afforded Medium BTO Alert. The population declines of many granivorous farmland birds have been linked with declines in survival outside the breeding season, probably caused by a lack of food in winter (Siriwardena et al 2000, Moorcroft et al 2002. There is, therefore, a real need to gain a better understanding of the winter ecology, habitat preferences and foraging behaviour of many of these species.…”
Section: Bird Detectability Using Perimeter Counts and Whole-area Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Meadow Pipit has also exhibited a population decline and has been afforded Medium BTO Alert. The population declines of many granivorous farmland birds have been linked with declines in survival outside the breeding season, probably caused by a lack of food in winter (Siriwardena et al 2000, Moorcroft et al 2002. There is, therefore, a real need to gain a better understanding of the winter ecology, habitat preferences and foraging behaviour of many of these species.…”
Section: Bird Detectability Using Perimeter Counts and Whole-area Seamentioning
confidence: 99%
“…The first method uses counts from the perimeter only ('perimeter counts'; Gillings et al 2005, Tucker 1992); the second involves walking parallel transects across the field sufficiently close together to ensure that everything is flushed and counted ('whole-area search'; Moorcroft et al 2002, Wilson et al 1996. For small-scale studies the more accurate whole-area search method is preferable but at larger scales, e.g.…”
mentioning
confidence: 99%
“…Others have demonstrated the role of weeds in sustaining biodiversity. For example, in Europe weeds found in stubble after grain harvest greatly affected the number of birds using the field, notably linnets (Carduelis cannabina; Moorcroft et al 2002), and loss of weeds is thought be one of a number of causes in the overall decline of birds in farmland . Work in the UK also revealed that arable weeds support high insect diversity reinforcing the need to balance weed control and biodiversity conservation .…”
Section: Integrated Weed Managementmentioning
confidence: 99%
“…These contrasts may, however, be explained by differing abundance and availability of grain and weed seeds on different cereal stubbles. Barley crops, for example, tend to have fewer herbicide applications than wheat crops, the structure of their stubbles is more open to foraging birds, and barley tends to shed more grain at harvest than wheat (Donald et al 2001, Moorcroft et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Seed-rich habitats such as over-winter stubbles and fodder crops have become scarce in modern farming landscapes, being replaced by autumn-sown cereals, silage and maize (Fuller 2000). Similarly, increasingly efficient harvesting, storage and seed cleaning, as well as intensive herbicide regimes, have reduced the abundance of grain and weed seed food on farms during the winter (Wildey et al 1999, Brickle & Harper 2000, Moorcroft et al 2002, Robinson & Sutherland 2002. Where seed-rich habitats remain on farmland, as on rotational set-aside fields, they are heavily selected by seed-eating birds in winter (Wilson et al 1996, Buckingham et al 1999, Hancock & Wilson 2003.…”
mentioning
confidence: 99%